The transformation of Sjafruddin Prawiranegara’s ideas on the people’s economy towards national economic independence‎ - Affandi, Faisal; Yafiz, Muhammad (Journal of Islamic Economics Lariba, 2025)
IntroductionIndonesia continues to face economic challenges such as income inequality, dependence on foreign capital, and marginalization of micro, small, and medium enterprises. These issues have reignited scholarly interest in economic models rooted in justice, ethics, and local empowerment. Sjafruddin Prawiranegara’s economic thought, centered on Islamic moral principles and people’s economy, offers a relevant framework for achieving national economic independence in today’s globalized context.ObjectivesThis study aims to explore the transformation and relevance of Sjafruddin Prawiranegara’s ideas on people’s economy as a foundation for developing a national economic model that prioritizes equity, inclusiveness, and independence from exploitative global capitalism.MethodA qualitative content analysis was conducted using 20 academic sources published between 2020 and 2024. Data were obtained through systematic searches using the Publish or Perish software and analyzed using thematic coding and triangulation. The analysis focused on identifying key themes related to people’s economy, Islamic ethical values, and economic independence.ResultsThe study finds that Sjafruddin emphasized an economy based on trust, moral responsibility, and equitable wealth distribution. His thought supports the development of MSMEs, cooperatives, and community-based institutions as pillars of a just economy. He also promoted Islamic principles such as the prohibition of usury and the use of zakat as tools for reducing inequality. His ideas remain relevant in addressing modern challenges such as digital transformation, green economy, and sustainable financial inclusion, especially through the empowerment of pesantren and grassroots movements.ImplicationsThis research illustrates that integrating Islamic moral economy into national development strategies can strengthen economic sovereignty and resilience. Policymakers and educators are encouraged to revisit Sjafruddin’s philosophy to inspire frameworks that center ethical values, justice, and local empowerment in economic governance.Originality/NoveltyThe study offers a novel reinterpretation of Sjafruddin Prawiranegara’s economic philosophy by connecting it to current socio-economic realities and development goals. It contributes to the intellectual revival of Islamic economic thought as a strategic alternative to mainstream capitalist and socialist models, positioning it as a path toward ethical and inclusive national economic independence.